The Use of Gemstones in The Chinese Community - Mohamed, Badaruddin; Lah, Salasiah Che; Azmi, Noor Azam (Humaniora, 2016)
This article aimed to provide documentation of information relating to local intelligence from the older generations, specifically the local intelligence of the Chinese community on gemstones.To better understand this issue, an informal interview had been conducted on an informant from the Chinese community who has vast experiences dealing with gemstone crafting. Literature reviews were also carried out to further understand the issue under discussion. It can be assumed that religion is the main factor influencing the use of gemstones among ancient Chinese. Although other aspects such as luck, prestige, and healing may also exist, the reasons would be solely based on the teachings of Buddhism. In summary, every God’s creations possess benefits and it is up to human to utilise them in either beneficial or adverse ways